Le détournement du genre policier sur la scène anglaise contemporaine : One Minute (2003) de Simon Stephens et Orphans (2009) de Dennis Kelly - Aloysia Rousseau (Sillages Critiques)
The expression detective play is not a valid critical category. It can at best be considered as an unfortunate collocation, derived from the canonical genre that is the detective novel. The whodunit is the only recurring expression in common critical vocabulary used to refer to the transposition of crime fiction to the stage, an obsolete expression which is obviously not a satisfying one when applied to contemporary detective plays such as Simon Stephens’ One Minute (2003) and Dennis Kelly’s Orphans (2009). There are no answers offered in Kelly’s and Stephens’ plays and violence is relegated to the offstage. These two playwrights are thus reinventing a genre, subverting the codes of both traditional detective fiction and the thriller. The investigations do not tend towards a solution but are structured around an absence, a void.